The Legacies of the Soviet Influence in the 1950s: China's 156 Major Industrial Projects - Zhangfeng Jin (Global Labor Organization (GLO), 2021)
This paper investigates whether and how China's adoption of Soviet-aided industrialization programs in the 1950s has affected its long-run innovation. Focusing on 156 major industrial projects aided by the Soviet Union, combined with an instrumental variable approach, I find that the adoption of these programs substantially discourages local firms to innovate in the long run. A causal mediation analysis of instrumental variable settings shows that the negative effect is entirely driven by local firms' lower intensity of incentive pay. This evidence suggests disadvantages of Soviet-aided industrialization programs for long-run innovation due to firms adopting incentive-incompatible management technology.
Keywords: O10; O30; L20; M52; 330; Soviet Aid; Technology Transfers; Incentive Pay; Innovation; China